THE SPECIFICS OF COMMUNICATIVE PROCESSES IN THE CONTEXT OF SOCIETY’S INFORMATIZATION - Skyba, Ivan (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
Introduction. In contemporary society, profound transformations are occurring due to the rapid development of science and technology and the introduction of cutting-edge information and communication technologies into various spheres of social practices. Overall, these transformations manifest in the accumulation of significant changes in various spheres of sociocultural activity and, primarily, they transform the very communicative (communication) sphere, thereby defining the specifics of modern communicative processes. The aim and tasks are to identify the specifics of communicative processes in the context of society’s informatization. Research methods. The theoretical and methodological basis of this study consists of general scientific and specialized methods and approaches, which will be used to investigate the specifics of communicative processes in the context of society’s informatization. Research results. In the context of society’s informatization, there is a rapid increase in communication channels and information exchange within society. However, the growth of technical capabilities for conducting communicative processes, in itself, does not lead to their success but rather expands and simultaneously complicates (diversifies) the system of their implementation. In this way, there is an unconscious shift of emphasis in communication from the communicative aspect to the technical or, at best, to the informational aspect, when there is a purely technical circulation of information without the corresponding communicative process. It is in this dimension that the key contradictions of the contemporary, so-called information society lie. Discussion. The discussion provides an analysis of Erich Fromm’s research in the context of facilitating communicative processes. Conclusions. The development of communication technologies accelerates the pace of life and intensifies communicative processes, leading to a clearer distinction and opposition between the informational and the genuinely communicative in processes of current communication. "Informational" and "communicative" have fundamentally different vectors of development. The presence of information does not automatically ensure communication, and in current conditions, within the established mass information-media culture, the genuinely communicative is becoming an increasingly problematic phenomenon.